Territorial Use Rights for Fisheries (TURF) in central-southern Chile: Their sustainability status from a transdisciplinary holistic approach. (October 2021) - Franco-Meléndez, Milagros; Cubillos, Luis A.; Tam, Jorge; Hernández Aguado, Simón; Quiñones, Renato A.; Hernández, Aldo
Abstract: The Territorial Use Rights for Fisheries (TURF) system are a kind of marine property where user rights are assiged to collective entities of artisanal fishers' organizations. But their effectivity continues to be limited, which demands a comprehensive evaluation of their social, economic, and ecological performance. Consequently, the practical integration and application of these aspects continue to be a significant challenge for their management. The "RAPFISH" multidimensional scaling technique was applied to assess the sustainability status of 19 TURFs of the Biobio Region (Chile), using 51 transdisciplinary attributes relating to ecological, economic, social, among other dimensions. The results obtained in the two-dimensional arrangement presented a sustainability gradient, due to the marked variations among the different TURFs, and only four cases had very weak sustainability scores. Broadly speaking, this study determined that the social dimension (score: 61.37%) had a "high" influence on the best performance of the TURF system, while the ecological, ethical, and institutional dimensions were rated from 'regular' to 'bad'. Overall, results indicate an average performance in the "medium" sustainability range (score: 54.68%), and these results generated questions about the TURFs' viability, mainly in those that have not reached their sustainability objectives. Therefore, more local studies are needed on the social dimension of this system, in order to define the effective participatory tools and social management plans in TURFs, which will contribute to improve their performance. Highlights: The performance of the TURFs system in the Biobio region. The transdisciplinary analysis on selected TURFs achieved an average sustainability (<70%). Fishers identified various attributes influencing the sustainability status of local TURFs. Strong bio-ecological and human relationships were inherent in responsible practices on TURFs. Ensuring new conceptual tools should be allocated to improve participation among stakeholders.